2011
DOI: 10.1016/j.toxicon.2011.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a metalloproteinase, Porthidin-1, from the venom of Lansberg’s hog-nosed pitvipers (Porthidium lansbergii hutmanni)

Abstract: Porthidium lansbergii hutmanni is a small pit viper found on Margarita Island, Venezuela. Local tissue damage is one of the most obvious characteristics of P. l. hutmanni envenomation, which can lead to diverse pathological effects, such as hemorrhage, edema, blistering, necrosis, lymphatic vessel damage and degradation of extracellular matrix. Metalloproteinases are one of the major components in venoms responsible for these effects. To date, very little is known or has been reported on P. l. hutmanni venom. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…In the haemorrhagic activity evaluation, which is one of the characteristic effects of Porthidium venoms (7,8,26,30,31), it was observed that the P.l.rozei venom exhibits a 13.87 ± 3.2 μg / mouse MHD, which is high when compared with previous reports for this genus (Table II), in which P. l. hutmanni (8) reported a 0.98 μg/mouse MHD. Porthidium nasutum from Costa Rica (32) obtained a 0.5 μg/mouse MHD, while Gutiérrez et al (33) reported a 1.6 μg/mouse MHD.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In the haemorrhagic activity evaluation, which is one of the characteristic effects of Porthidium venoms (7,8,26,30,31), it was observed that the P.l.rozei venom exhibits a 13.87 ± 3.2 μg / mouse MHD, which is high when compared with previous reports for this genus (Table II), in which P. l. hutmanni (8) reported a 0.98 μg/mouse MHD. Porthidium nasutum from Costa Rica (32) obtained a 0.5 μg/mouse MHD, while Gutiérrez et al (33) reported a 1.6 μg/mouse MHD.…”
Section: Discussionmentioning
confidence: 67%
“…A number of reports in the literature have documented different levels of variation in the composition of Porthidium venom (7,8). These differentiations may be related to phylogenetic or taxonomic discrepancies, age, size, geographic location, diet, seasonal variations, variations associated with sex, among others, all these lead to divergences in the quantity and quality of the venoms.…”
Section: Introductionmentioning
confidence: 99%
“…Porthidium hyoprora is a representative of this group of venomous snakes; their habitat is the Amazon tropical forest in Brazil, Ecuador, Peru and Colombia [ 3 ]. Proteomic analysis of P. nasutum and P. ophryomegas snake venom and the characterization of toxins from P. lansbergii hutmanni [ 4 , 5 ] have already been performed. However, minimum attention has been paid to the characterization of P. hyoprora venom.…”
Section: Introductionmentioning
confidence: 99%
“…The crude Lmm venom and the CMS-5 fraction were run in electrophoresis under reduced conditions (8 -20 %), using methods [10,12,22] to detect the proteins. For the crude Lmm venom, the polypeptides found were classified into groups, based on their relative molecular masses, establishing that the very high ones were greater than 200 kilodaltons (kDa), high between 200 -66.2 kDa, intermediate 66.2 -21.5 kDa and low between 21.5 -6.5 kDa and very low those below 6 kDa [6].…”
Section: Polyacrylamide Gel Electrophoresismentioning
confidence: 99%